Gender Difference of the Relationship between Arterial Stiffness and Blood Pressure Variability in Participants in Prehypertension - Yang Lan; Huan Liu; Jinbo Liu; Hongwei Zhao; Hongyu Wang (International Journal of Hypertension)
Aim. The association of pressure load with elasticity in vascular system has not been studied fully. We proposed a hypothesis whether gender could modify the association of blood pressure variability (BPV) and arterial stiffness assessed by carotid-femoral pulse wave velocity (CF-PWV) in prehypertensive patients. Methods. 24h ambulatory blood pressure monitoring (24h-ABPM) and CF-PWV were measured in 723 participants with prehypertension. Univariate and multivariate regression analyses of these clinical and biological parameters were performed in total population, male and female. Results. A total of 723 participants (mean age 59.76 ± 12.37years, male 329 and female 394) were enrolled into the study. Compared with female, body mass index (BMI), fasting plasma glucose (FPG), uric acid (UA), and homocysteine (HCY) were significantly higher (all p < 0.05). Arterial stiffness (CF-PWV, male versus female, 10.89 ± 2.50 versus 10.33 ± 2.13 m/s, p=0.004) and BPVs (male versus female, 24 h SBPV 13.2 ± 5.11 versus 13.03 ± 5.20; 24 h DBPV 10.34 ± 3.87 versus 9.64 ± 3.59; N SBPV 11.90 ± 6.60 versus 10.94 ± 4.79; N DBPV 9.64 ± 5.87 versus 8.20 ± 4.48, all p<0.05) were higher in male. Multivariable linear regression analysis showed that 24 h BPV were linearly and positively related to CF-PWV in total population (24h SBPV, B=0.033; 24 h DBPV, B=0.035, both P<0.05) and female (24h SBPV, B=0.041; 24h DBPV, B=0.067, both P<0.05) independent of traditional risk factors and medications. Conclusion. BPV was independently associated with arterial stiffness in total population and the relation was modified by gender. 24 h BPVs in prehypertensive patients were useful to identify the early arterial stiffness. Clinical Trials Registration. This trial was registered with Clinical Trials.gov Identifier: NCT02569268.